2012
DOI: 10.1186/1758-5996-4-49
|View full text |Cite
|
Sign up to set email alerts
|

Associations of the TNF-alpha -308 G/A, IL6 -174 G/C and AdipoQ 45 T/G polymorphisms with inflammatory and metabolic responses to lifestyle intervention in Brazilians at high cardiometabolic risk

Abstract: BackgroundCytokines secreted by the adipose tissue influence inflammation and insulin sensitivity, and lead to metabolic disturbances. How certain single-nucleotide polymorphisms (SNPs) interfere on lifestyle interventions is unclear. We assessed associations of selected SNPs with changes induced by a lifestyle intervention.MethodsThis 9-month intervention on diet and physical activity included 180 Brazilians at high cardiometabolic risk, genotyped for the TNF-α -308 G/A, IL-6 -174 G/C and AdipoQ 45 T/G SNPs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 53 publications
(57 reference statements)
1
11
0
Order By: Relevance
“…Only one study has been designed with a surgical intervention; a surgical study with bariatric procedure (21) has shown that this polymorphism is not related to biochemical outcomes after a massive weight loss with a biliopancreatic diversion procedure. All previously cited studies have been conducted in Caucasian subjects, and only one study has evaluated a dietary intervention in a different ethnicity (22). In this design, -308 G/A SNP predisposed a better response of glucose metabolism to a dietary intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Only one study has been designed with a surgical intervention; a surgical study with bariatric procedure (21) has shown that this polymorphism is not related to biochemical outcomes after a massive weight loss with a biliopancreatic diversion procedure. All previously cited studies have been conducted in Caucasian subjects, and only one study has evaluated a dietary intervention in a different ethnicity (22). In this design, -308 G/A SNP predisposed a better response of glucose metabolism to a dietary intervention.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study only assessed the genetic influence on IR using HOMA-IR under a codominant model and not the genetic influence on blood glucose. Furthermore, other studies [13,16,19,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] regarding the association between the ADIPOQ T45G polymorphism and IR have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In the eligible studies, 12 studies were held in Europe [14, 16, 21, 24-26, 29, 31-34, 36], 11 in Asia [13, 15, 17-20, 22, 23, 27, 28, 30], and 1 in Brazil involved white and non-white subjects [35]. All subjects in 2 [28,31] and 3 [13,21,29] studies were male and female, respectively.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we found an association of IL-6 SNPs with an increased risk of developing lumbar disc herniation. Genetic variations in the IL-6 promoter region could result in aberrant IL-6 transcription and expression (Fishman et al, 1998), thereby affecting individual susceptibility to various diseases (Curti et al, 2012). For example, the IL-6-572C/G polymorphism leads to replacement of cytidine by guanosine in the IL-6 promoter (Kitamura et al, 2002;MullerSteinhardt et al, 2004;Hamid et al, 2005;Lei et al, 2005), affecting IL-6 transcription and, in turn, changing IL-6 expression (Terry et al, 2000).…”
Section: Ld and Haplotype Value Between Snpsmentioning
confidence: 98%